2014
DOI: 10.1159/000358521
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum 25-Hydroxyvitamin D Levels and TTN

Abstract: Aim: To investigate the association between serum 25-hydroxyvitamin D (25(OH)D3) levels and transient tachypnea of the newborn (TTN). Methods: Calcium (Ca), phosphorus (P), alkaline phosphatase (ALP), parathormone (PTH) and serum 25(OH)D3 levels were measured in 51 infants diagnosed with TTN and 59 healthy control infants for comparison. Demographic factors including gestational age, birth weight, gender, delivery mode, parity, vitamin D supplementation during pregnancy and severity of TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
2
3
0
5
Order By: Relevance
“…Similar results were found in the study done by Konca et al in 2014 in which serum vitamin D levels were studied in infants diagnosed as TTN and those without TTN and found that the serum levels of 25(OH)D3 were significantly lower in infants with TTN compared to infants with no respiratory distress (p<0.01). 30 The fetus is dependent on the mother for vitamin D in utero (the 25(OH)D3 crosses the placenta). 31 In our study we found statistically significant role of supplementation of vitamin D in pregnancy on serum vitamin D levels in neonates as these neonates were less deficient in vitamin D as compared to neonates whose mothers were not supplemented.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results were found in the study done by Konca et al in 2014 in which serum vitamin D levels were studied in infants diagnosed as TTN and those without TTN and found that the serum levels of 25(OH)D3 were significantly lower in infants with TTN compared to infants with no respiratory distress (p<0.01). 30 The fetus is dependent on the mother for vitamin D in utero (the 25(OH)D3 crosses the placenta). 31 In our study we found statistically significant role of supplementation of vitamin D in pregnancy on serum vitamin D levels in neonates as these neonates were less deficient in vitamin D as compared to neonates whose mothers were not supplemented.…”
Section: Discussionsupporting
confidence: 88%
“…15. Similar results were found in the study done by Konca et al in 2014 in which serum vitamin D levels were studied in infants diagnosed as TTN and those without TTN and found that the serum levels of 25(OH)D3 were significantly lower in infants with TTN compared to infants with no respiratory distress (p<0.01). 30 The fetus is dependent on the mother for vitamin D in utero (the 25(OH)D3 crosses the placenta).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…tik anne bebeği ve D vitamini eksikliği yer almaktadır (1)(2)(3) . Vitamin D kalsiyum, fosfor metabolizması üzerine önemli etkilerinin yanında antiinflamatuvar ve antienfektif özellikleri de olan steroid yapıda bir hormondur (4) .…”
unclassified
“…18,19 Literatürde tek bir çalışmada YGT olan bebeklerde 25(OH)D 3 düzeyi sağlıklı kontrollere göre anlamlı olarak düşük bulunmuştur. 20 Bu çalışmada, hem neonatal hem de maternal vitamin D eksikliğinin YGT gelişimine etkisi olup olmadığı irdelenmiştir. Kliniğimizde belirlenen tarih aralığında 1.238 doğum gerçekleşmiş olup, bu doğumların 842'si sezaryen doğum idi.…”
unclassified